Duwar Rābithah al Thalabah fi 'Insya' al Bī'ah al Lughawiyah bi Ma'had al Yusriyah - Muhammad Ardiansyah (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2022)
The Role of the Student Association in creating a linguistic environment at the Al-Yusriyah Islamic Boarding School. The purpose of this article is to obtain information about the Arabic language environment (Bi'ah Lughawiyah) conducted by the Al-Yusriyah Islamic Boarding School Santri Organization Pangkalan Susu. This research focused on the Arabic environmental method (Bi'ah Lughawiyah) in terms of: the objectives of the Arabic environmental method (Bi'ah Lughawiyah), the forms of activities in the Arabic language environment (Bi'ah Lughawiyah). This research method is qualitative by using interview, observation and documentation techniques. The data were analyzed by means of the analysis of Miles and Hubermen. The data validation technique used a triangulation process, namely, triangulation of various sources (from students who are administrators of the Al-Yusriyah Islamic Boarding School Santri Organization and non-management and teachers). The results of this research indicate the Arabic language learning method using the language environment method as well as the forms of activities in the language environment itself, namely mufrodat, muhadatsah, language classes, language dramas and language courts